Percutaneous Coronary Intervention of bifurcation lesions: The proof is in the pudding!. Issue 6 (29th November 2022) - Seth, Ashok; Ezhumalai, Babu
Key Points: Provisional stenting strategy is the most common technique for treatment of bifurcation lesion in the 'real world' patients undergoing percutaneous coronary intervention. The technical success appears to be lower in provisional stent strategy compared to upfront two stent strategy due to worsening of the ostial side branch lesions after main branch stenting; following wire recrossing and side branch dilation/stent implantation stenting leads to equivalent procedural success and in hospital outcomes. Side branch access after main branch stenting is technically challenging and an algorithmic approach helps to achieve procedural success.